REVEALING THE IMPLICIT MEANING OF LANGUAGE STYLE IN MADURESE PROVERBS - Wardatin, Fajriyah Novi; Setiawan, Slamet (Universitas Islam Sumatera Utara (UISU), 2022)
Proverb is categorized as the simplest form of myriad types of folklore. It is used to express the truth based on the traditional saying, which has some implicit meanings. One of the interesting proverbs to be investigated is the Madurese proverb connecting with some crucial life principles. The present study is aimed to reveal the implicit meaning of Madurese proverbs, which have a special meaning on foregrounding values. The study has designed a qualitative method and used the theory of conversational implicature, pioneered by Grice (1989). The analysis and the pragmatics approach are elaborated since the data were gained using the extracted method. The findings show that Madurese proverbs can be categorized as two common types of implicature: generalized conversational implicature and particularized conversational implicature. The results also reveal that those chosen proverbs represented three main Madurese social principles: (i) courage (ii) upholding the honor of moral values, and (iii) upholding self-dignity.